KOMUNITAS RAYAP TANAH DI SEPULUH LOKASI DI DKI JAKARTA - Ginuk Sumarni; Agus lsmanto (Jurnal Penelitian Hasil Hutan, 1987)
Subterranean  termites  are important  insects which attack structural   timber.  Six species have been found at ten locations of the Jakarta Metropolitan: Microtermes insperatus, M. incertoides, Odontotermes  javanicus, Macrotermes gilvus, Schedorhinotermes javanicus, and Coptotermes  curvignathus. Various termite species prevail in two of the locations (P. Rebo and P. Minggu). M. insperatus was found to be the largest population in every location. Cempaka  Putih  was the lowest in similarity  and diversity  indexes of the termite  species. The same  termite species  was found in Kramat  Jati and Kebayoran Baru. No subterranean  termites  were found in Cilincing, Tanjung  Priok, and Kemayoran